From Late to MTE: Alternative Methods for the Evaluation of Policy Interventions - Thomas Cornelissen; Christian Dustmann; Anna Christina Raute; Uta Schönberg (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper provides an introduction into the estimation of Marginal Treatment Effects (MTE). Compared to the existing surveys on the subject, our paper is less technical and speaks to the applied economist with a solid basic understanding of econometric techniques who would like to use MTE estimation. Our framework of analysis is a generalized Roy model based on the potential outcomes framework, within which we define different treatment effects of interest, and review the well-known case of IV estimation with a discrete instrument resulting in a local average treatment effect (LATE). Turning to IV estimation with a continuous instrument we demonstrate that the 2SLS estimator may be viewed as a weighted average of LATEs, and discuss MTE estimation as an alternative and more informative way of exploiting a continuous instrument. We clarify the assumptions underlying the MTE framework and illustrate how the MTE estimation is implemented in practice.
Keywords: C26; I26; 330; marginal treatment effects; instrumental variables; heterogeneous effects